![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x^2-2x+1 3x^4-8x^3-10x^2+8x-5 x^2-2x-16/3 3x^4-2x^3+x^2 -6x^3-12x^2+8x-5 -6x^3+4x^2-2x -16x^2+10x-5 -16x^2+32/3x-16/3 -2/3x+1/3
Vậy
- (3x4-8x3-10x2+8x-5):(3x2-2x+1) = \(x^2-2x-\frac{16}{3}\)dư \(\frac{-2}{3}x+\frac{1}{3}\)
x^2-1 x^4-2x^3+2x-1 x^2-2x+1 x^4-x^2 -2x^3+x^2+2x-1 -2x^3+2x x^2-1 x^2-1 0
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (x4-2x3+2x-1):(x2-1) = \(\frac{\left(x^4-1\right)-\left(2x^3-2x\right)}{x^2-1}\)
= \(\frac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}\) =\(\frac{\left(x^2-1\right)\left(x^2+1-2x\right)}{x^2-1}\)
= \(x^2+1-2x\)= \(\left(x-1\right)^2\)
b, (8x3-6x2-5x+3):((4x+3)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x^3-8x^2+3x+2 3x+1 x^2-3x+2 3x^3+x^2 - -9x^2+3x+2 -9x^2-3x - 6x+2 6x+2 - 0
Vậy (3x3-8x2+3x+2) : (3x+1) \(=x^2-3x+2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x-2)(x-1) = x(2x+1) + 2
⇔ x2 - x - 2x + 2 = 2x2 + x + 2
⇔ x2 - 2x2 - x - 2x - x = 2 - 2
⇔ -x2 - 4x = 0
⇔ x(-x - 4) = 0
⇔\(\left[{}\begin{matrix}x=0\\-x-4=0\end{matrix}\right.\)
⇔\(\left[{}\begin{matrix}x=0\\x=-4\end{matrix}\right.\)
b) (x+2)(x+2) - (x-2)(x-2) = 8x
⇔ x2 + 2x + 2x + 4 - x2 + 2x + 2x - 4 = 8x
⇔ 8x = 8x
⇒ x có vô số nghiệm
c) (2x-1)(x2-x+1) = 2x3-3x2+2
⇔ 2x3 - 2x2 + 2x - x2 + x -1 = 2x3 - 3x2 + 2
⇔ 3x = 3
⇔ x = 1
d) (x+1)(x2+2x+4) - x3 - 3x2 + 16 = 0
⇔ x3 + 2x2 + 4x + x2 + 2x + 4 -x3 - 3x2 +16= 0
⇔ 6x + 20 = 0
⇔ x = \(-\frac{20}{6}\)
.e) (x+1)(x+2)(x+5) - x3-8x2=27
⇔ (x2 +2x + x+2)(x+5) -x3-8x2=27
⇔ (x2 + 3x + 2)(x+5)-x3 - 8x2 = 27
⇔ x3 + 5x2 + 3x2 + 15x + 2x + 10 - x3 - 8x2 =27
⇔ 17x = 17
⇔ x = 1
\(=\left(2x^3-x^2+4x^2-2x-6x+3\right):\left(2x-1\right)\\ =\left[x^2\left(2x-1\right)+2x\left(2x-1\right)-3\left(2x-1\right)\right]:\left(2x-1\right)\\ =x^2+2x-3\)